Left-right dissociation of hippocampal memory processes in mice. - Shipton, O; El-Gaby, M; Apergis-Schoute, J; Deisseroth, K; Bannerman, D; Paulsen, O; Kohl, M (National Academy of Sciences, 2014)
Left-right asymmetries have likely evolved to make optimal use of bilaterian nervous systems; however, little is known about the synaptic and circuit mechanisms that support divergence of function between equivalent structures in each hemisphere. Here we examined whether lateralized hippocampal memory processing is present in mice, where hemispheric asymmetry at the CA3-CA1 pyramidal neuron synapse has recently been demonstrated, with different spine morphology, glutamate receptor content, and synaptic plasticity, depending on whether afferents originate in the left or right CA3. To address this question, we used optogenetics to acutely silence CA3 pyramidal neurons in either the left or right dorsal hippocampus while mice performed hippocampus-dependent memory tasks. We found that unilateral silencing of either the left or right CA3 was sufficient to impair short-term memory. However, a striking asymmetry emerged in long-term memory, wherein only left CA3 silencing impaired performance on an associative spatial long-term memory task, whereas right CA3 silencing had no effect. To explore whether synaptic properties intrinsic to the hippocampus might contribute to this left-right behavioral asymmetry, we investigated the expression of hippocampal long-term potentiation. Following the induction of long-term potentiation by high-frequency electrical stimulation, synapses between CA3 and CA1 pyramidal neurons were strengthened only when presynaptic input originated in the left CA3, confirming an asymmetry in synaptic properties. The dissociation of hippocampal long-term memory function between hemispheres suggests that memory is routed via distinct left-right pathways within the mouse hippocampus, and provides a promising approach to help elucidate the synaptic basis of long-term memory.